Rock mechanics in petroleum engineering : proceedings SPE/ISRM International Conference, 29-31 August 1994 - EUROCK '94 : SPE/ISRM International Conference (1994 : Delft, Netherlands); Society of Petroleum Engineers (United States); International Society for Rock Mechanics (Rotterdam : A A Balkema, 1994)
51